Chronic Noncancer Pain and the Long Term Utility of Opioids - CPN Watson; JH Watt-Watson; ML Chipman (Pain Research and Management)
OBJECTIVE: To report on a long term experience in treating patients with chronic noncancer pain (CNCP).